ENT600: Online queue alert system / Nur Farhana Abdul Samat … [et al.] - Abdul Samat, Nur Farhana; Abd Rahman, Rosenah; Shamsudin, Shahida; Che Mohamed Sukri, Siti Nafisah; Abdul Gani, Siti Norfahana (2018)
The executive summary is usually short and concise. The summary articulates what the opportunity conditions are and why they exist, who will execute the opportunity and why they are capable of doing so, how the company will gain entry and market penetration. The case study is discussed about surgical ward at University Malaya Medical Centre (UMMC) operates the process of admission and discharge services. There are lots of issue that related with delayed of process admission and discharge. This issue is deeply will investigate the main factor that contributed in delayed of these processed and identify the solution. Hospitals can combine process management with information technology to redesign patient flow for maximum efficiency and clinical outcomes. These surgical ward known as 6U unit that are dealing with Electronic Medical Record (EMR) which involved the computerized systems. Therefore, the operational strategies has been apply in the 6U unit to identify the quality objective in order to lessen the client waiting time and enhance the bed management. Hospitals intend to deliver good quality of care and also work efficiently. To ensure this, there needs to be a good fit between patient needs and nursing staff on 6U unit. Besides, SWOT analysis and Consumer Trend Canvas has been used in this case study. By using these two method analysis will overcome the process of admission and discharge problems. All admissions and discharges of the hospital should be centrally managed and planned, as single-department solutions may create or worsen bottlenecks in other areas. Improved pre-admission information would be a first important step to optimize the admission process. Managers of other hospitals can supplement the results of this study with their own process analyses, to improve their own patient admission processes.